114 Sleep disordered breathing (SDB) and intracranial pressure (ICP) monitoring in children with craniosynostosis. (December 2018) - Russo, K; Samuels, M; Davies, M; Stagg, S; Laverty, A; Abel, F; Jeelani, O; Dunaway, D; Hayward, R; James, G
Abstract : Introduction: Raised ICP is a recognised complication of craniosynostosis in children and may reduce cerebral blood flow and consciousness, as well as causing papilledema and other neurological symptoms. Obstructive sleep apnoea (OSA) has a reported prevalence of between 40% and 85% in children with syndromic craniosynostosis (SC) and it is known that SDB can further raise ICP. Since 2015 we have routinely carried out simultaneous sleep studies (SS) for children undergoing ICP monitoring and we wanted to examine further the relationship between ICP and SDB in this group. Methods: We reviewed a new clinical service combining ICP measurement with respiratory polygraphy (RP). Patients with relevant symptoms were selected by the neurosurgery team and underwent placement of subdural ICP bolt under general anaesthetic followed by placement of respiratory polygraphy (RP) sensors in the late afternoon on the 1 st or 2nd night of a 48 hour ICP recording. Results: A total of 27 patients (19 M: 8 F) were identified, with a mean age of 5.7 years (range 1.3 years to 18.2 years). The indications for ICP insertion and the clinical syndrome are shown in table 1(a) and 1(b) respectively. All studies were successful with no signal loss. The sleep study (SS) and ICP outcome, as well as the neurosurgical outcome, can be seen in table 1(c). Discussion: Some studies showed important relationships between ICP and SDB, although the severity of OSA did not predict those who had high ICP or required surgery. Importantly, ICP in these patients may be significantly affected by sleep stage and in operated patients, by transient physiological rises in CO2.